2012
DOI: 10.1371/journal.pone.0034514
|View full text |Cite
|
Sign up to set email alerts
|

F-Actin-Dependent Regulation of NESH Dynamics in Rat Hippocampal Neurons

Abstract: Synaptic plasticity is an important feature of neurons essential for learning and memory. Postsynaptic organization and composition are dynamically remodeled in response to diverse synaptic inputs during synaptic plasticity. During this process, the dynamics and localization of postsynaptic proteins are also precisely regulated. NESH/Abi-3 is a member of the Abl interactor (Abi) protein family. Overexpression of NESH is associated with reduced cell motility and tumor metastasis. Strong evidence of a close rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
5
12
0
Order By: Relevance
“…Smaller fibers have an increased mobile fraction of recovery compared to larger fibers. Altering the stability of actin bundles, either through chemical perturbation, and under-or over-expression of actin binding proteins can change the recovery of actin in FRAP experiments (Bae, Sung, Cho, & Song, 2012;Lorente, Syriani, & Morales, 2014;Pappas, Krieg, & Gregorio, 2010;Zweig & Singer, 1979). In the spermatheca, the mobile fraction of small fibers was around 60%, which is consistent with the mobile fractions of actin recovery seen in the leading edge of lamellipodia in highly motile cancer cells during migration (Lai et al, 2008;Lorente et al, 2014).…”
Section: Discussionsupporting
confidence: 59%
“…Smaller fibers have an increased mobile fraction of recovery compared to larger fibers. Altering the stability of actin bundles, either through chemical perturbation, and under-or over-expression of actin binding proteins can change the recovery of actin in FRAP experiments (Bae, Sung, Cho, & Song, 2012;Lorente, Syriani, & Morales, 2014;Pappas, Krieg, & Gregorio, 2010;Zweig & Singer, 1979). In the spermatheca, the mobile fraction of small fibers was around 60%, which is consistent with the mobile fractions of actin recovery seen in the leading edge of lamellipodia in highly motile cancer cells during migration (Lai et al, 2008;Lorente et al, 2014).…”
Section: Discussionsupporting
confidence: 59%
“…The recovery rate at each time point was determined by dividing the relative intensity of ROI at each time point by the average of the relative intensity of ROI of 3 images taken before photo bleaching. Mobile fraction (MF) was calculated using the equation as follows [13][14][15] : MF D (F end -F post )/(F pre -F post ), where F end is the relative intensity of fluorescence at the endpoint, F post is immediately after photo-bleaching, and F pre is before photo-bleaching.…”
Section: Fluorescence Recovery After Photobleaching (Frap)mentioning
confidence: 99%
“…Then, Matsuda et al reported that NESH/Abi-3 expression enhanced metastasis in the presence of an Abl inhibitor, imatinib mesylate [ 18 ]. More recently, Bae et al reported that NESH/Abi-3 directly binds to F-actin, and regulates dendritic spine morphogenesis and synapse formation in rat hippocampal neurons [ 19 , 20 ]. These results indicate that NESH/Abi-3 is somehow involved in the regulation of the actin cytoskeleton, but the mechanism remains elusive.…”
Section: Introductionmentioning
confidence: 99%